2016
DOI: 10.1063/1.4964842
|View full text |Cite
|
Sign up to set email alerts
|

Radiative recombination mechanisms in polar and non-polar InGaN/GaN quantum well LED structures

Abstract: We study the photoluminescence internal quantum efficiency (IQE) and recombination dynamics in a pair of polar and nonpolar InGaN/GaN quantum well (QW) light-emitting diode (LED) structures as a function of excess carrier density and temperature. In the polar LED at 293K, the variation of radiative and non-radiative lifetimes is well described by a modified ABC type model which accounts for the background carrier concentration in the QWs due to unintentional doping. As the temperature is reduced, the sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…It has been shown that radiative recombination in polar InGaN/ GaN QWs grown on c-plane sapphire substrates is bimolecular, meaning that excitonic effects can be neglected. 23 Since our LEDs are grown this way, we assume that the radiative recombination rate in the active QWs is equal to Bn 2 , where B 300 = 1 × 10 −10 cm 3 s −1 is the radiative recombination coefficient at room temperature (300 K) and n is the photoexcited carrier density. 5,6,12 We note that this estimate for B includes corrections that are required to accommodate photon recycling, 24 which will vary with device structure and optical design.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…It has been shown that radiative recombination in polar InGaN/ GaN QWs grown on c-plane sapphire substrates is bimolecular, meaning that excitonic effects can be neglected. 23 Since our LEDs are grown this way, we assume that the radiative recombination rate in the active QWs is equal to Bn 2 , where B 300 = 1 × 10 −10 cm 3 s −1 is the radiative recombination coefficient at room temperature (300 K) and n is the photoexcited carrier density. 5,6,12 We note that this estimate for B includes corrections that are required to accommodate photon recycling, 24 which will vary with device structure and optical design.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…A fundamental assumption of the ABC model is, that the three coefficients A, B, and C are constant. However, there are recent indications that this is not necessarily the case, for instance the non-radiative lifetime (inverse of A) increases with increasing carrier density [24][25][26]. Also the radiative recombination is expected to increase at high current densities, when screening of the internal fields in the QW increases the wave function overlap (and thus B).…”
Section: A Theorymentioning
confidence: 99%
“…We have identified two bands in PL spectra of our structures, the faster blue and a slower defect bands, which differ by most properties, such as by their spectral position and width, lifetime, and sensitivity to diverse type of excitation. The fast blue QW band has luminescence time in the order of nanoseconds and has probably still excitonic nature, as our QWs are designed to be shallow and thin . The slower defect band has luminescence response in the microsecond time scale which is not desired in fast scintillator applications.…”
Section: Introductionmentioning
confidence: 99%
“…The fast blue QW band has luminescence time in the order of nanoseconds and has probably still excitonic nature, as our QWs are designed to be shallow and thin. [6] The slower defect band has luminescence response in the microsecond time scale which is not desired in fast scintillator applications. Although luminescent nitride structures have been widely used for a long time, the luminescent properties of the defect bands in bulk GaN and InGaN/GaN QW structures are not well understood, because this defect band can be observed only for very low excitation densities which are not subject of interest for LED focused research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation